Penerapan Pajak Pertambahan Nilai 11% Dan Pendapatan Usaha Mikro Kecil Menengah Di Kota Bitung - Pesak, Pricilia Joice; Miran, Michael; Gazali, Ahmad; Salindeho, Alfred (Jurnal Ilmiah Raflesia Akuntansi, 2024)
The higher the VAT rate is set, the more difficult it is to get the desired income because these UMKM still use the actual selling price without adding the price before VAT, when the price after VAT is recorded, it is difficult for the buyers to know the exact price amount and most of the buyers do not pay the VAT charged and this will affect the UMKM income because the income which should be a profit but becomes a loss because it has to cover the VAT rate charged to the buyer will be deposited with the government. This study aims to test whether the application of VAT affects UMKM's income. Based on the results of hypothesis testing, it is known that the sig value is 0.004 <0.05 and the t-table is 1.701, so 3.127> 1.701, which means that the application of VAT affects the income level of a UMKM. The results showed that the application of 11% VAT affects the income level of an MSME, which means that the higher the VAT rate, the more it will affect the income of an MSME